Leadership Competence and Teacher Job Satisfaction: Evidence from Structural Path Analysis in Indonesian Public Senior High Schools - Eri Deka Gustiar; Mukhtar Latif; Zawaqi Afdal Jamil (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This experimental study investigated the effectiveness of Process Oriented Guided Inquiry Learning (POGIL) based Student Worksheets in enhancing metacognitive skills among eleventh grade students learning Chemical Equilibrium. Utilizing a one group pretest posttest design with 36 participants, the intervention implemented specially designed worksheets integrating POGIL's inquiry cycle with explicit metacognitive scaffolding. Metacognitive skills comprising planning, monitoring, and evaluating components were measured through validated essay instruments before and after four instructional sessions. Statistical analysis using the Wilcoxon Signed Rank Test revealed a significant improvement in overall metacognitive skills (Z = -5.197, p < 0.001, large effect size d = 2.47). Notably, 94.44% of students demonstrated measurable progress, with normalized gain scores indicating high improvement in planning (g = 0.82), moderate improvement in evaluating (g = 0.51), and moderate improvement in monitoring (g = 0.48). These findings substantiate that POGIL based worksheets, when designed with intentional metacognitive prompts, effectively foster the development of higher order regulatory skills essential for mastering complex chemical concepts. The study contributes to science education literature by demonstrating how inquiry based pedagogies can be optimized for metacognitive skill development.